Written reports of adverse events in acute care—A discourse analysis. Issue 4 (27th May 2019) - Gyberg, Anna; Henoch, Ingela; Lepp, Margret; Wijk, Helle; Ulin, Kerstin
Abstract: Adverse health care events are a global public health issue despite major efforts, and they have been acknowledged as a complex concern. The aim of this study was to explore the construction of unsafe care using accounts of adverse events concerning the patient, as reported by patients, relatives, and health care professionals. Twenty‐nine adverse events reported in an acute care setting in a Swedish university hospital were analyzed through discourse analysis, where the construction of what was considered to be real and true in the descriptions of unsafe care was analyzed. In the written reports about unsafe events, the patient was spoken of in three different ways: (a) the patient as a presentation of physical signs, (b) the patient as suffering and vulnerable, and (c) the patient as unpredictable. When the patient's voice was subordinate to physical signs, this was described as being something that conflicted with patient safety. The conclusion was that the patient's voice might be the only sign available in the early stages of adverse events. Therefore, it is crucial for health care professionals to give importance to the patient's voice to prevent patients from harm and not unilaterally act only upon abnormal physical signs.